Tests of thermal macroeconomic theory on simulated microeconomies - Yihang Luo; R S MacKay; Nick Chater (Journal of Physics: Complexity)
In this paper, we test predictions of a new theory of macroeconomics, called ‘thermal macroeconomics.’ The theory aims to apply the mathematical structure of classical thermodynamics, including analogues of temperature and entropy, to predict aspects of the aggregate behaviour of populations of economic agents without analysing their detailed interactions. We test the theory by comparing its predictions with the behaviour of a variety of simulated micro-economies in which goods and money can be exchanged between agents, confirming the predictions of the theory. The paper serves also to illustrate and make more tangible the predictions of thermal macroeconomics.